Association between magnesium intake and cognition in US older adults: National Health and Nutrition Examination Survey (NHANES) 2011 to 2014 - Meng‐Hua Tao; Jialiang Liu; Diana Cervantes (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Identifying nutrition‐ and modifiable lifestyle‐based risk factors for cognitive decline and dementia may contribute future primary prevention strategies. This study aimed to evaluate the associations between magnesium intake and cognition in older adults in the United States. Methods Based on the National Health and Nutrition Survey (NHANES) between 2011 and 2014, the study included 2508 participants aged 60 years and older. Linear regression models were used to examine the association of total magnesium intake with cognition. Results After adjusted demographic and other confounding factors, intakes of energy and total calcium, and serum vitamin D level, higher intake of total magnesium was independently associated with 0.15 higher global cognitive z‐score (95% confidence interval, 0.02 to 0.28 for highest vs. lowest quartile, P trend = .037). The positive association of total magnesium intake with global cognition was primarily presented among women, non‐Hispanic Whites, and those with sufficient serum vitamin D levels (≥50 nmol/L), although interactions were not significant. There were no clear linear associations for global cognition with serum vitamin D level. Discussions Our findings suggest that high magnesium intake alone may improve cognition in older adults, particularly among non‐Hispanic Whites and subjects with sufficient levels of serum vitamin D. Further studies are needed to confirm the findings.